Transformasi Manusia Perahu - Ical Ical; Wa Ode Sifatu; Hartini Hartini (JURNAL KABANTI: Kerabat Antropologi, 2024)
Boat people are humans who depend on the sea for their lives. This study aims to determine; 1) the life pattern of the boat people in Bajo Indah Village.  The data were analyzed qualitatively descriptively, then presented in the form of a narrative. The results of this study indicate that; 1) There was a change in the lifestyle of the boat people in the village of Bajo Indah caused by the establishment of a tourist area around the coast of Bokori island and the shift of residence from the coast to the mainland of Konawe, namely the village of Bajo Indah. This change in lifestyle can be seen from several aspects, namely; a) changes in livelihoods, b) changes in the education system, c) changes in residence, and d) changes in culture/traditions.